URGENSI AUDITOR SYARIAH PADA INDUSTRI KEUANGAN SYARIAH - Ivahzada Marella Edgina (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The Islamic finance industry has gained international recognition as part of the global financial system. The Islamic finance industry has developed rapidly over the last few decades. To be able to maintain the existence and trust of users and the general public, the Islamic finance industry must comply with sharia regulations to ensure that business activities and other corporate activities comply with sharia principles. Therefore, sharia auditors play an important role in maintaining transparency and public trust in the integrity of the Islamic finance industry as an Islamic institution. Sharia audit has a major interest in the Islamic finance industry. With the existence of a sharia audit in the industry, it will prove that the industry is in the right industry in accordance with Islamic teachings.